2010
DOI: 10.1111/j.1468-3083.2010.03634.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergy is not the main trigger of urticaria in children referred to the emergency room

Abstract: The children with urticaria are frequently referred to the paediatric emergency room, but only in a few cases were associated with severe clinical manifestations or allergy. The evidence of an inverse relationship between the number of accesses and the patients' age may be explained by the higher prevalence of this disease in early childhood and possibly also by a higher concern of the parents of the younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
3
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 6 publications
4
23
3
7
Order By: Relevance
“…The most common etiologic factors in children with acute urticaria include acute infections, food, insect bites, and parasitic infections, respectively (11,14,(17)(18)(19). In our study, the triggering factors we found were similar to those in many studies in the literature.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The most common etiologic factors in children with acute urticaria include acute infections, food, insect bites, and parasitic infections, respectively (11,14,(17)(18)(19). In our study, the triggering factors we found were similar to those in many studies in the literature.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, the rate of oral corticosteroid use was reported as 20% by Ricci et al (14), the rate of intravenous corticosteroid use was reported as 27%, and oral corticosteroid use was reported as 18.9% by Liu et al (11). Lee et al (28) reported treatment unresponsiveness with normal dose H1-AH in 50% of patients in their study of 98 children with chronic urticaria.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Rarely is food allergy the cause of chronic urticaria and can typically be excluded on the basis of clinical history. Common triggers/aggravating factors/associations for exacerbations of chronic urticaria are intercurrent viral infections [14] and psychological factors [15]. The aetiological classification of chronic urticaria/angioedema is given in Table 2.…”
Section: Aetiologymentioning
confidence: 99%